Oleuropein ameliorates hyperlipidemia, oxidative stress, inflammatory and liver dysfunction biomarkers, in streptozotocin-induced diabetic rats - Nema A. Mohamed, Marium M. Hussein, Osama M. Ahmed, Suhailah S. Al-Jameel, Hessah M. Al-Muzafar, Kamal Adel Amin, Heba M. Abdou (Journal of Applied Pharmaceutical Science, 2024)
Diabetes mellitus (DM) is a serious threat factor for chronic liver disorders and the development of nonalcoholic steatohepatitis into cirrhosis. However, numerous pharmacological actions of olive polyphenol have been discovered, with oleuropein being a primary phenolic substance found in olive leaves, olive oil, and olive fruit (Olea europaea). Our goal is to identify the impacts of oleuropein on lipid measurements, oxidative stress, serum leptin, adiponectin levels, inflammatory status, and hepatic dysfunctions in a male rat model with streptozotocin (STZ)-induced DM. Oleuropein was orally administered to diabetic rats at a 5 mg/kg bw/day dose for 15 days. Diabetic rats treated with oleuropein demonstrated improved hepatic function test results (ALT, AST, alkaline phosphatase, and bilirubin), while activity of the low liver glucose-6-phosphate dehydrogenase (G6PDH) increased. Moreover, serum triacylglycerol, very low-density lipoprotein, low-density lipoprotein, and total cholesterol (TC) were considerably reduced, while high-density lipoprotein increased markedly. In addition, serum antioxidative enzymes such as glutathione peroxidase, catalase, glutathione-S-transferase, and superoxide dismutase increased, as well as glutathione levels. Lipid peroxidation levels were lower than those in the STZ control group. Treating diabetic rats with oleuropein not only resulted in decreased serum leptin and increased adiponectin levels but also had a substantial inhibitory effect on the elevated COX-2 and TNF-α mRNA expression levels in the livers of the STZ group. In conclusion, oleuropein has shown promising results in mitigating hyperlipidemia, oxidative stress, inflammation, and hepatic dysfunction biomarkers in diabetic rats.
Keywords: Diabetes mellitus, oleuropein, liver, antioxidants, inflammation, rats